EFISIENSI KERJA SAMA PENJAMINAN PEMBIAYAAN BANK SYARIAH DI LEMBAGA PENJAMINAN SYARIAH - Ulfa Dwi Nurfajrina; Atina Shofawati (Universitas Airlangga, 2019)
This research purpose to analyze of financing guarantee cooperation agreement between PT. Jamkrindo Syariah Surabaya Branch and Islamic Banks. This research also analyze the comparison of the efficiency level of Islamic Bank to measure the performance of each Sharia banks. Efficiency measurement is calculated using the Data Envelopment Analysis (DEA) method with an intermediation approach. The results showed that the implementation of such cooperation was not entirely in accordance with the DSN-MUI and OJK, while the results of efficiency level analysis of the four Islamic bank partners showed that there was one bank that had an efficiency value less than 1 (inefficiency), so that the performance was not optimal. Whereas other Sharia banks have achieved perfect efficiency of 100%, which means they have achieved optimal performance.Keywords: Efficiency, Data Envelopment Analysis (DEA),Financing Guarantee, Islamic Bank